Klasifikasi Sistem dan Hubungan sebagai Inti dari Sistem - Fachruddin Fachruddin; Makmur Syukri; Anisa Maulidya; Dermawan Syahputra (Transformasi Manageria: Journal of Islamic Education Management, 2023)
The system is a collection of objects that have relationships with each other. The components in this system must be integrated with each other. As a result, the most important factor in integrating existing components in a system is the relationship. The purpose of this study is to examine the system's classification and relationships as the core of the system. This study uses a qualitative approach with library research and is included in the qualitative research category. Sources of research data were obtained from related books and journals as well. Data collection techniques include collecting literature data or library materials related to the discussion in the research. The results of this study indicate that there are eight system classifications, and relationships are the core of the system. Keywords: System Classification, System Core Relations, Systems Approach